RISK MANAGEMENT IN VOLCANO TOURISM IN INDONESIA - Sigit Cahyadi, Hery (ASEAN Journal on Hospitality and Tourism, 2014)
Indonesia is a country that is located in the Pacific Ring of Fire and three continental plates. It makes Indonesia has a lot of volcano with its beautiful crater. Today, the volcanoes not only attract the researchers to come but also attract people for the purpose of tourism and recreation. The beautiful sceneries and the unique landscapes make the volcanoes become a tourist destination. But the lack of risk management in that destination gives some contributions to the accidents to the tourist. A qualitative data analysis was conducted in this research and a survey and literature review method used to identify the risk management that was conducted by volcano tourism destination. The aim of the study is to identify how the volcano tourism destinations in Indonesia managed in its relationship to decrease the accidents in volcano tourism